Penyusunan Strategi Digital Marketing dan Penerapan Promotion Mix terhadap UMKM Rasa 244 - Muhammad Donal Mon; Jennifer Jennifer (ConCEPt - Conference on Community Engagement Project, 2023)
Rasa 244 is a business that was established since 2001 by Mr. Akun. There are various dishes in this Mr. Akun, namely capcay, special fried noodles, special fried kwetiau, special fried rice, and others with a 100% halal label. The method used to find out the problems that occur in Rasa 244 is the observation and interview method, so the problems that occur in Rasa 244 belonging to Mr. Akun are the lack of digital marketing strategies and promotion mix Rasa 244 is still not well-known by the public. Based on the problems that occur, the next step is to design using a digital marketing strategy and the application of a promotion mix, namely by creating a social media account in the form of Instagram as a direct marketing medium, doing advertising on Instagram so that the surrounding community can get to know Rasa 244 with affordable dishes, create a menu list and brochures that are as attractive as possible so that old and new customers can find out about additions and changes to the menu and prices contained in this Rasa 244 and the distribution of brochures to the surrounding community as a public relations.